2021
DOI: 10.3390/ijms22041986
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities, Challenges and Pitfalls of Using Cannabidiol as an Adjuvant Drug in COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may lead to coronavirus disease 2019 (COVID-19) which, in turn, may be associated with multiple organ dysfunction. In this review, we present advantages and disadvantages of cannabidiol (CBD), a non-intoxicating phytocannabinoid from the cannabis plant, as a potential agent for the treatment of COVID-19. CBD has been shown to downregulate proteins responsible for viral entry and to inhibit SARS-CoV-2 replication. Preclinical studies have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 278 publications
(338 reference statements)
0
35
0
Order By: Relevance
“…Moreover, CBD did not show anxiolytic or antidepressive effects, which also does not confirm previous literature showing anxiolytic properties of this dose. 5,[16][17][18][19][20][21] However, as in the case of inflammation, patients did not have high anxiety and depression levels at baseline (mean GAD-7 and PHQ-9 scores < 10). In addition, all the patients received significant support, with repeated visits of nurses at the residence and remote daily monitoring by the physician.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CBD did not show anxiolytic or antidepressive effects, which also does not confirm previous literature showing anxiolytic properties of this dose. 5,[16][17][18][19][20][21] However, as in the case of inflammation, patients did not have high anxiety and depression levels at baseline (mean GAD-7 and PHQ-9 scores < 10). In addition, all the patients received significant support, with repeated visits of nurses at the residence and remote daily monitoring by the physician.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the pandemic, several editorials, reviews, and pre-clinical studies have suggested that cannabidiol (CBD), a nonpsychotomimetic phytocannabinoid, could have potential beneficial effects in the course of COVID-19. [1][2][3][4][5][6] CBD has putative anti-inflammatory properties [7][8][9][10][11][12][13][14] and may attenuate the cytokine storm by reducing the levels of cytokines (such as interleukin-6, IL-6; tumor necrosis factor-a, TNF-a; and interferon-c) and symptoms of acute respiratory distress syndrome in a mouse model, frequent clinical conditions observed in patients with severe COVID-19. 7,8 CBD reduced brain levels of cytokines (such as TNF-a 9 and IL-1b 10 ) and microglia activation, [10][11][12] and decreased the levels of proinflammatory cytokines (IL-5, IL-6, and IL-13) in pre-clinical models of lung inflammation 13 and allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other antioxidant compounds that have been proposed as potential adjuvants in COVID-19 are zinc [ 260 ], selenium [ 261 ], melatonin [ 262 ], curcumin [ 263 ], N-acetylcystein [ 264 , 265 ], GC4419, a SOD mimetic [ 266 ], colchicine [ 267 ], α-lipoic acid [ 268 ], glutathione [ 269 ], broccoli or glucoraphanin capsules [ 270 ], dypiridamole [ 271 ], cannabidiol [ 272 ], combinations of vitamin D, magnesium, and vitamin B12 [ 273 ], and diammonium glycyrrhizinate with vitamin C [ 274 ].…”
Section: Antioxidants As Neuroprotectors In Patients Infected With Covid-19mentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2), a SARS-CoV receptor and transmembrane serine protease 2 (TMPRSS2), a cell surface protein, allow entry and S protein priming of SARS-CoV-2, respectively, thereby providing viral gateways ( Figure 4 ) and viral activation in lung tissue, oral and nasal mucosa, and the gastrointestinal tract [ 155 , 156 , 157 , 158 ], and even facilitate mother to fetal transmission of the virus [ 159 ]. ACE2 enzyme binds glycoprotein S1, the characteristic viral spike protein, via a receptor-binding domain, and TMPRSS2 permits entrance of the virus into the cytoplasmic membrane of host cells [ 160 , 161 ]. Investigations also revealed that SARS-CoV-2 M pro (the main protease) has a pivotal role in viral replication and transcription and can be regarded as an attractive drug target [ 162 , 163 ].…”
Section: Antiviral Activity: Special Focus On Sars-cov-2mentioning
confidence: 99%